Synthesis of novel Fe3O4 nanostructures surrounded by Ti-MOF nanostructures as bioactive and efficient catalysts in three-component synthesis of new pyrazole derivatives - Qubais Saeed, Balsam; Waleed, Ibrahem; Chlib Alkaaby, Hussein Humedy; Farhan Jawad, Sabrean; Altimari, Usama S.; Ahmed AL-Sarraj, Ziyad Shihab; Shbeeb, Ruwaida T.; Hadrawi, Salema K.; Suliman, Muath; Alshahrani, Mohammad Y. (Frontiers in Materials, 2023)
Synthesis and reporting of new nanoparticles with diverse properties is important in chemistry. A one-step, rapid and controllable synthesis of the new Fe3O4 surrounded in Ti-MOF nanostructures was carried out with microwave technology. After identifying and confirming the structure, Fe3O4 surrounded in Ti-MOF nanostructures was used as a suitable catalyst with high thermal resistance and recyclable in a three-component reaction of phenylhydrazine, malononitrile and aldehyde to synthesis novel pyrazole derivatives. Continuing investigations on Fe3O4 surrounded in Ti-MOF nanostructures, its antimicrobial properties were tested on Gram-positive bacterial species, Gram-negative bacterial species and fungi bacterial. Identification of Fe3O4 surrounded in Ti-MOF nanostructures with morphology and size distribution technique (SEM), surface area technique (BET), Infrared spectroscopy (FT-IR), Energy-Dispersive X-ray spectroscopy (EDX/EDX mapping), and Vibrating Sample Magnetometer (VSM) were performed. Synthesized pyrazole derivatives with Fe3O4 surrounded in Ti-MOF nanostructures than previously reported methods have less synthesis time and high efficiency. In antimicrobial properties high effects were observed based on MIC, MBC, and MFC values.